Literacy of lower social classes at the turn of the century: Letters in the First World War - Schell, Csilla (Ethnographica et Folkloristica Carpathica, 2020)
The paper discusses the literacy of lower classes in the last decades of the Austro-Hungarian Empire and focuses on the correspondence of the First World War. Besides briefly reviewing the general contexts for the literacy of lower social classes (education, legislation), the paper discusses language/ethnicity issues as well. By summarizing linguistic remarks from selected research papers, the author underlines that the large number of letters was due to the increased need for communication and these pieces of writing reflect the literacy and the language of the masses; consequently, wartime correspondence is an accurate reflection of the communication of lower social classes.